The Role of the Ismuhu Yahya Mosque in Helping the Government for the Welfare of the Community Through the “Pasar Bahagia” Program - Riwayati, Anny; Juminta, Juminta; Rizki, Abang Dede Predi; Rahmaniah, Syarifah Ema; Herlan, Herlan (PINISI Discretion Review, 2023)
The economic system adopted by Indonesia based on Pancasila and the 1945 Constitution has the implied meaning of placing the people in a noble position. An economy that always prioritizes the people with the principles of social justice or a just and prosperous society. An idea emerged from the community, namely in the Ismuhu Yahya Mosque area to move the Indonesian economy by launching the "Pasar Bahagia" program. It aims to help the government eradicate poverty. The Ismuhu Yahya Mosque, located in Parit Baru Village, Kubu Raya, West Kalimantan, is also in the midst of a heterogeneous society, both religion and ethnicity. The role of the village head in providing support for ideas made by the mosque makes everything run smoothly without any friction with the community in general. The method used in this study is to use qualitative methods using descriptive analysis. By conducting interviews with the mosque, beneficiaries of the “Pasar Bahagia” program, and village heads. The result obtained from the "Pasar Bahagia" program is the creation of a happy society, because there is basic food assistance and vegetables that can be used to meet basic needs for one or two days. In addition, there are many benefits from a health perspective, people become mentally healthy and increase their faith so that when they return home, they can spread positive energy in their surroundings. The village head also feels very grateful for the presence of the Ismuhu Yahya Mosque. It is hoped that the role of mosques in all regions can be optimized for the welfare of the community.